ANALISIS AKUNTANSI PERSEDIAAN PADA TOKO SIAGA PEKANBARU - Olifia, Tasya; ', Sumarno; ', Srikartikowati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Shop Siaga Pekanbaru engaged in trade that sells school and office supplies. The main problem is the recording in the accounting and inventory valuation, accurate record keeping is required to produce accurate financial statements in accordance with PSAK No.14, because the methods used in assessing the inventory menctatat and assist management in making decisions in order to avoid shortages and overages that always to meet customer needs. This kind of research included qualitative descriptive research. The data used is secondary data, documentation and archives of the company in 2016. The collected data were analyzed descriptively. The results showed lower essentially Store Inventory Accounting Alert Pekanbaru has applied PSAK No.14 well, including record keeping and inventory valuation and the disclosures in the financial statements. As for who has not been in accordance with PSAK 14, such as the absence of inventory costs, other costs and conversion costs on measurement inventory, costs standard on measurement techniques, the absence of a recovery back to the recognition as an expense.Keyword : inventory accounting , PSAK No. 14 ( Revised 2008 )